Leukotriene B4 limits the effectiveness of fish oil in an animal model of asthma. Issue 11 (November 2021) - Miranda, D.T.S.Z.; Zanatta, A.L.; Miles, E.A.; Calder, P.C.; Nishiyama, A.
Abstract: This study aimed to evaluate the levels of eicosanoids derived from arachidonic acid (ARA) in the lungs of asthmatic rats supplemented with fish oil. The present data gives insight into the action of fish oil in asthma, related to its inability to modify the contractile capacity of tracheal smooth muscle reported previously in a model of asthma in rats. Male Wistar rats were supplemented daily with 1 g of fish oil/kg of body weight for 21 days. They were exposed to ovalbumin (OVA) after previous sensitization with OVA to induce asthma. Pulmonary levels of five eicosanoids were measured using immunoassay kits: PGE2, TXB2, LTB4, LXA4, and 8-iso PGF2α . In asthmatic rats, supplementation with fish oil resulted in lower concentrations of lung eicosanoids produced by cyclooxygenase-2 and 15-lipoxygenase: PGE2, TXB2, and LXA4, respectively. Fish oil supplementation also decreased the non-enzymatically produced eicosanoid 8-iso PGF2α . Fish oil supplementation did not affect LTB4, a metabolite of 5-lipoxygenase. The limited efficacy of fish oil supplementation in asthmatic rats is associated with a lack of action in reducing the levels of LTB4 in the lungs. Thus, fish oil differentially modulates the concentrations of eicosanoids derived from ARA via specific pathways in an animal model of asthma. Highlights: Unraveling the action of fish oil in the lungs of asthmatic rats. Fish oil modifies inflammatory pathways with enzymatic specificity. Leukotriene B4 remains unchanged with fish oil supplementation in asthmatic rats. Abstract : Fish oil, Asthma, Eicosanoid, Leukotriene.